Organizing Ontalan Tradition in Madurese Customs - Sulalah, Anis; Hariyanto, Erie; Hamzah, Moh. (KARSA Journal of Social and Islamic Culture, 2022)
The Ontalan tradition is a Maduranese tradition of throwing money to the bride and groom at the bridal events, which its people still preserve. The Ontalan practice is unique in its implementation because it only involves the groom’s family, relatives, and bhle. In contrast, the bride is not obligated to carry it out. Research was included in empirical legal research, namely studying and analyzing legal behavior, both individuals and society. The research method used by the researcher was qualitative. This research intended to understand the phenomena experienced by describing them in words and language in a particular natural context using various scientific methods. As empirical legal research, the approach used by researchers is a socio-legal approach. This research showed that Ontalan was first carried out at the groom’s house at the time of the bridal events, one day after its events. The groom’s family and relatives carried out the parties. The money given is not thrown away but is delivered using an envelope. Second, they carry out Ontalan to continue their ancestral heritage, help the bride and groom, reject lousy luck, and strengthen friendship because it does not conflict with religion. The benefits of implementing Ontalan were to create a spirit of social care through giving alms, bringing family relationships closer, strengthening ties, and making an equal household; those who do not implement Ontalan will receive social sanctions. Third, religion and culture are interrelated from the sociological perspective of Islamic law. The term Ontalan is a social definition because the actual social fact of Ontalan is a gift that, in its implementation, aims to create social change through efforts to help the bride and groom build harmonious and equal family relationships. Using the ‘Urf theory, the Ontalan tradition is included in ‘urf shahih because it does not conflict with sharia, benefits the practitioners, and contains religious values.